Word Order, Action, and the Brain: A Reply to Arbib - Kemmerer, David (Language and linguistics compass, 2015)
In a recent paper in this journal, I argued that the crosslinguistic prevalence of subject–object–verb and subject–verb–object word orders reflects the sequential and hierarchical representation of action in Broca's area. Arbib (2015) discusses that paper in the context of broader computational, neuroscientific, and evolutionary issues, and presents a critique of my specific proposal. Here, I respond to his concerns and defend my original account.